Sexual Exploitation in Marriage Tourism: Justice and Legal Protection for Victims in Cianjur and Jember - Muhammad Faisol; Sri Lumatus Saadah; Martha Eri Safira; Lailatul Mufidah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
This article aims to provide recommendations for establishing regional regulations related to tourist marriage, the imposition of strict sanctions, and efforts to protect victims. The urgency of this research is because, in several tourist areas, there has been a practice of contract marriage involving women and children with tourists for years. This research uses descriptive-qualitative data analysis with a case study approach. In contrast, data collection techniques are done through interviews and a literature review of online source data. Based on the results of the research, it was found that contract marriage cases in the Puncak Bogor area and the Jember area are one type of sexual trafficking with child victims involving marriage brokers, parents, and tourists. This marriage is motivated by economic factors to save themselves and their families from poverty. Victims are primarily virgin girls aged 14-18 years who are married off on a transactional basis in exchange for half of the promised dowry. In practice, marriages are conducted are not registered. The local government in Jember has passed a local regulation on protecting women and children, while in Cianjur a district head regulation on the prohibition of contract marriages was passed. Socialization from the Religious Affairs Office and local government is still done in tourist areas. However, some contract marriage practices can still be found because women do not feel they are victims of sexual trafficking. This research provides a basis for local government policy towards handling and minimizing the practice of contract marriage.